A tutela penal da representatividade democrática: a criminalização do financiamento ilícito de partidos políticos - Teodoro, Frediano José Momesso (2017)
The relentless struggle for power has prompted political parties and their members to pursue resources whose amounts are increasingly staggering. The illegal provenance of campaign funds has been revealed in recent years, demonstrating that irregularities in political parties funding are tied to a wide range of previous crimes. The economic power abuse is such in political-electoral campaign across the globe that democratic representativeness is seriously compromised, mainly by unfair electoral competition process and by popular sovereignty relativization. Faced with the urgency of the lawless political financing issue and the ineffectiveness of the current rule, it is recognized the imperativeness of declare it as criminal offense. Consequently emerges the need to justify the criminalization of offensive actions against democratic representativeness, free democratic elections and others equally democratic institutes. In order to achieve such an aim, it is proposed to acknowledge the referred democratic institutes as assets protected against the economic power abuse by the criminal law. Through the application of harm principle theory, as guiding the present study, it is possible to justify the criminalization of democratic regime violations by the economic power abuses